Extraction and characterization of Malaysia pandan leaves by soxhlet method - Siti Nor Fazruaini, Rusli (2011)
Research in finding more sources for specialty oils have been actively conducted nowadays . In this study, Soxhlet Extraction method is one of the extraction technique can be used to extract a soluble fraction from solid medium into an organic solvent such n-hexane and ethanol. In this research, the soxhlet extraction method used to extract the pandan leaves ( Pandanus Amaryllifolius Roxb.) . This leaves was selected because of it is easily find in our local market. To produce high extract yield of the leaves, parameters that affect the performance of the soxhlet extraction method were investigated. The manipulated parameters were pandan leaves surface area and the solvent extractant. The yield was observed. Grind leaves produced higher yield compared to non-grinding leaves. In addition, ethanol was found to be better solvent than n-hexane. Both extraction were using ethanol and n-hexane.